Fabrication of 3D graphene/MoS2 spherical heterostructure as anode material in Li-ion battery - Wenelska, Karolina; Adam, Viktor; Thauer, Elisa; Singer, Lennart; Klingeler, Rüdiger; Chen, X.; Mijowska, E. (Frontiers in energy research, 2022)
Three-dimensional (3D) graphene-based nanocomposites have received considerable attention in both fundamental research and industrial applications, as they combine the functionalities of well-controlled nano-architectures and the integrity of bulk materials. Actually, among these materials, spherical structures are attracting more and more attention worldwide due to their excellent performance in various fields such as drug delivery, heterogeneous catalysis, encapsulation of support, and electrode materials for lithium-ion batteries. Herein, a facile route to fabricate a three-dimensional hierarchical graphene/MoS2 nanocomposite is presented. The molecular heterostructure is derived from graphene oxide flakes and precursors of molybdenum ((NH4)2Mo7O4·4H2O) and sulfur (L-cysteine). Spherical morphology (GO/MoS2) is obtained via self-assembly of the precursor. This 3D nanocomposite exhibits MoS2-nanosheets strongly linked to graphene oxide flakes, which renders it particularly suited to exploit the conversion reaction of MoS2 for electrochemical energy storage. When assembled into an electrode in lithium-ion batteries, as-prepared GO/MoS2 electrodes indeed deliver a high initial charge capacity of 783 mA h g−1 at a current density of 100 mA/g and Coulombic efficiency of more than 96% from the second cycle on exceeding the theoretical capacity of the pristine 2D MoS2 and graphene. Overall, the study sheds some light on the design of 3D heterostructure as a promising anode material in Li-ion batteries.